Mesofauna density in seagrass meadows of Changuu Island (Zanzibar Archipelago, Tanzania) during nutrient enrichment and macrofauna exclusion experiment - Agustín Moreira-Saporiti; Mirta Teichberg; Aoife O extquotesingleSullivan (PANGAEA, 2026)
Mesofauna density was sampled during a nutrient enrichment and macrofauna exclusion experiment. A total of 24 plots were set up parallel to the shore, with presence of the three seagrass species (Syringodium isoetifolium, Thalassodendron ciliatum and Thalassia hemprichii) in each plot. The experiment was the factorial combination of two treatments: macrofauna exclusion using cages (three levels: open, closed and uncaged) and nutrient enrichment using garden NPK fertilizer (two levels: ambient and enriched). Each treatment combination was replicated four times. Exclusion treatment simulates the consequences for the food web of losing a top predators and macrograzers. Nutrient enrichment was simulated by issuing nitrogen-phosphorus-potassium (NPK) [15:9:20] fertilizer pellets. NPK fertilizer fast release pellets were packed into cotton tubes and then into a perforated plastic tubes to simulate slow release of nutrients. The tubes were buried half-way into the sediment to ensure enrichment of both the water column and the sediment. Data was collected between July 19th and September 20th of 2017 in four sampling times. Day 0 (19.07.2017), Day 20 (09.08.2017), Day 38 (31.08.2017) and Day 63 (19.09.2017). Data collection and experiment took place in Changuu Island (Zanzibar Archipelago, Tanzania; 0611 extquotesingleS, 3916 extquotesingleE). Changuu Island is located 3 km from Stone Town, Zanzibar extquotesingles busiest town. Changuu remains relatively unaffected by nutrient runoff pollution. The study area is characterised by a fringing reef around a multi-specific seagrass ecosystem. The substrate is primarily carbonate sediment. Average water depth is approximately 30 cm at Spring Low and 5 m at Spring high tide with an average depth of 2 m. Mesofauna density was measured in each experimental plot to study the effect of nutrient enrichment and macrofauna exclusion on the seagrass associated mesofauna. To determine the mesofauna density, mesofauna was sampled in each treatment plot by collecting one seagrass shoot per species at each treatment plot at all sampling times. Each shoot was collected in a white mesh bag (<1 mm mesh size). Once in the laboratory, each bag was placed on a laboratory tray, turned inside out, and rinsed with local seawater. The resulting tray then contained the seagrass shoot and any mesofauna that was attached to the seagrass and the sampling bag. Any mesofauna attached to the leaves of the seagrass shoot was carefully removed with forceps. Mesofauna were sorted into taxonomic groups (gastropods, amphipods, polychaetes, isopods, nudibranchs, bivalves and decapods), counted and measured for size (mm). The abundance of each taxonomic group was calculated per seagrass species shoot (individuals/shoot). This result was multiplied by the shoot density of each seagrass species in each plot and then summed to get individuals m-2 for each taxonomic category.